Analysis on Current Status and Countermeasures for Laboratory Animal Management in Sichuan Province Based on Administrative Licensing - CHEN Bing; ZOU Yixing; WANG Jingdong (Shiyan dongwu yu bijiao yixue)
Laboratory animals are indispensable strategic resources that support technological progress and innovation. At the same time, the biosafety of laboratory animals is an important component of national public health security. The production and use of laboratory animals require statutory administrative licensing. This article first summarizes the current status of management and development in Sichuan Province by reviewing the number, types, and industry distribution of license-holding facilities, the area of facilities and the status of top ten largest facilities by area, the types and quantities of laboratory animals produced, and the production capacity of certain facilities, as well as the types and quantities of laboratory animals used and the status of the top ten facilities by animal quantity. Then, it discusses the development advantages of the laboratory animal industry in Sichuan Province, including its leading industrial scale in the western region, increasing regional influence, and emerging comprehensive benefits. However, there are significant issues such as the inability of laboratory animal production to adequately meet the demand, the need to improve the level of technological innovation, and the challenges of ensuring animal safety management. Finally, corresponding countermeasures suggestions are proposed, including actively supporting the improvement of quality and efficiency of laboratory animal production, establishing a stable support mechanism for technological innovation, and placing a strong emphasis on animals safety management. This article aims to provide a reference for further improving the management level and industry development momentum of laboratory animals in Sichuan Province and other provinces.